Tinjauan Kapasitas Dan Pelayanan Pada Pelabuhan Ferry: Studi Kasus Pada Pelabuhan Ina Marina Di Kecamatan Kota Masohi, Kabupaten Maluku Tengah - Isak Lilipory; Jacob Breemer; Sri Utami Meladya Eko (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
Ina Marina Ferry Port in Kota Masohi plays an important role in connecting various islands in the Central Maluku Regency and serves as the main access point for residents and tourists traveling to destinations across the Maluku region. The purpose of this research is to identify internal and external factors that influence the port's capacity and services, and to analyze its facilities, including the waiting area and parking lot. The findings show that Ina Marina Ferry Port has several strengths, such as its strategic location, adequate pier, affordable tariffs, and basic facilities. However, weaknesses were identified, including a limited waiting area, the absence of gender-separated toilets, inefficiencies in the ticketing system, and inadequate facilities for larger vehicles. Externally, the port faces opportunities such as increasing passenger demand, development of new routes, potential investment, and tourism partnerships, alongside threats including competition, government regulations, weather conditions, environmental risks, and rising operational costs. Capacity analysis using the arithmetic method indicates that the waiting area and motorcycle parking lot will not meet the projected demand in 2034, while facilities for four-wheel and six-wheel vehicles remain adequate. Service analysis using SWOT places the port in Quadrant III (WO), suggesting that the main strategy is to leverage external opportunities to address internal weaknesses.Keywords : Capacity, Service, Ina Marina Port, Arithmetic, SWOT